Bioremediation of hydrocarbon contaminated soil using indigenous hydrocarbon degrading fungi - Mohd Farith, Kota (Universiti Malaysia Sarawak, UNIMAS, 2010)
Hazardous pollutants such as Polycylic Aromatic Hydrocarbons (PAHs) which can be found in motor oil, have strained public concerns as PAHs are toxic, mutagenic and also carcinogenic. Bioremediation has been the best option for converting these hazardous pollutants into less hazardous compounds by utilizing microorganisms. In this research, Bionectria sp. was chosen for bioremediation of used motor oil in soil. Time of incubation, percentage of inoculums, moisture content of the soil, and percentage of oil use has been optimized for the bioremediation process. Bionectria sp. was inoculated for degrading used motor oil at different percentage, 3 %, 5 %, and 10 % together with different moisture content of soil, 40 % and 60 % for six weeks. Remaining used motor oil extracted out from soil using toluene and the optical density was checked. The best result was given by sample with 8 % (v/w) of inoculum – 60 % of moisture content – 10 % (v/w) used motor oil used with 91 % of the used motor oil degraded.